Open field exposure facilitates consummatory extinction - Justel, Nadia (2016)
During extinction the organism learns that a conditioned stimulus or a conditioned response is no longer associated with an unconditioned stimulus, and as a consequence a decrement in the response is presented. The exposure to novel situations (e.g. exploration of a novel open field) has been widely used to modulate (i.e., either enhance or deteriorate) learning and memory. The goal of the present study was to test if open field exposure could modulate consummatory extinction. The results indicated that open field exposure accelerated the extinction response (i.e., experimental subjects given novelty exposure had lower consummatory behavior than control subjects) when applied before ? but not after ? the first extinction trial, or when applied before the second extinction trial. The results suggest that environmental treatments such as novelty exposure provide a valuable, non-pharmacological alternative to potentially modulate extinction processes.